Analysis of retail marketing strategies on organizational competitiveness - Odera, Odhiambo (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The purpose of this study was to analyze retail marketing strategies on organizational competitiveness. The study attempted to examine the strategies that have been applied and adopted by the retail companies elsewhere in attempt to understand how retailing functions. A descriptive research design was employed in this study. The population was marketing executives in the selected bottling companies in Kenya. Primary data was collected using closed questionnaire. The data collected was organized and presented using descriptive statistics. Correlation analysis was also utilized for data analysis. Findings indicate that the most pursued retail marketing strategies were; marketing segmentation, product strategies, distribution, pricing, marketing relationship and promotions. The findings also suggest that bottling companies rely on combination of strategies as different market segments respond differently hence need for product-specific marketing strategy.